The problem of pain investigation in the literature of CIS countries - Tsymbalyuk, V. I.; Tretyak, I. B.; Sapon, N. A.; Krychun, S. B.; Prykhodko, V. I. (Ukrainian Neurosurgical Journal, 2005)
Medical literature on the pain problems in which the mechanisms of pain development, classification of pain types, methods of pain conservative and surgical treatment were studied, served as the basis of this review. The sources from the Institute scientific library include works, that have been published in countries of CIS for the last 5 years.